A fluorescein-based fluorescence probe for the fast detection of thiol. Issue 23 (8th June 2016) - Liu, Yunchang; Xiang, Kaiqiang; Tian, Baozhu; Zhang, Jinlong
Graphical abstract: We designed a asymmetric fluorescein-based probe for the detection of thiol using 2, 4-dinitrobenzenesulfonyl (DNBS) group as the detection group. The probe shows nonfluorescence when connected with 2, 4-dinitrobenzenesulfonyl which destroys the π-conjugation and its fluorescence appears when the probe reacts with thiol. Highlights: A fluorescein-based fluorescent probe for detecting thiols is synthesized. The probe shows good selectivity toward thiols compared with many other amino acids. The probe can detect thiols even with the disturbance of quantity of other amino acids. The color changes from colorless to yellow which can be checked by naked eyes. Abstract: A new turn-on fluorescent probe for the selective detection of thiol over other amino acids was synthesized. Probe possesses the widely-used thiol-selective 2, 4-dinitrobenzenesulfonyl (DNBS) group which can react with thiol and release the fluorescein which has strong fluorescence. Fluorescein, a well known xanthene fluorescent dye, has two states at different environment. Fluorescein is in the state of spirocyclization when connected with 2, 4-dinitrobenzenesulfonyl (DNBS) group which has no fluorescence. However, it is in the state of open form when it reacts with thiol which has a strong fluorescence. The transition of the two states can be used to selectively detect thiol and the color can change from colorless to yellow which can be differentiated by naked eyes. Upon the titration of thiol, the absorption band at 454 nm rises gradually and the fluorescence emerges at 521 nm and the detection limit can be as low as 0.16 μM. All of such good properties prove it to be a good sensor for the selective detection of thiol and it shows a potential use in bioimaging applications.